2021
DOI: 10.3390/children8111011
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexia Telerehabilitation during the COVID-19 Pandemic: Results of a Rhythm-Based Intervention for Reading

Abstract: The COVID-19 outbreak necessitated a reorganization of the rehabilitation practices for Learning Disorders (LDs). During the lockdown phase, telerehabilitation offered the possibility to continue training interventions while enabling social distancing. Given such an advantage of telerehabilitation methods for LDs, clinical research is still needed to test the effectiveness of diverse teletraining approaches by comparing their outcomes with those of face-to-face interventions. To compare the effectiveness of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 48 publications
(56 reference statements)
0
26
0
2
Order By: Relevance
“…The rank of “Chinese” had a dramatic increase from 49th in 2000–2016 to 32nd in 2017–2021. It is also worth mentioning that “executive function” ( 107 , 108 ), “morphological awareness” ( 109 , 110 ), “Meta-analysis,” “decoding” ( 16 ), “dyscalculia,” “EEG” ( 111 , 112 ), “Eye tracking” ( 113 , 114 ), “rhythm” ( 115 , 116 ), “bilingualism” ( 117 , 118 ), and “functional connectivity” ( 119 , 120 ) entered the top 50 high-frequency keywords in 2017–2021, suggesting that these topics may become the new research hotspots.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rank of “Chinese” had a dramatic increase from 49th in 2000–2016 to 32nd in 2017–2021. It is also worth mentioning that “executive function” ( 107 , 108 ), “morphological awareness” ( 109 , 110 ), “Meta-analysis,” “decoding” ( 16 ), “dyscalculia,” “EEG” ( 111 , 112 ), “Eye tracking” ( 113 , 114 ), “rhythm” ( 115 , 116 ), “bilingualism” ( 117 , 118 ), and “functional connectivity” ( 119 , 120 ) entered the top 50 high-frequency keywords in 2017–2021, suggesting that these topics may become the new research hotspots.…”
Section: Resultsmentioning
confidence: 99%
“…With the rapid development of the Internet, more knowledge is mainly obtained through network resources, and the effect of dyslexia on "information seeking" behavior has gradually attracted the attention of dyslexia researchers (132,133). In addition, the emergence of a new keyword COVID-19 in the past 2 years also showed that during the COVID-19 epidemic, researchers began to study the impact of the epidemic on dyslexia research (115,(134)(135)(136)(137). As the international exchange of dyslexia research continues to grow, scientists are aware that differences in education-related legislation in different countries may lead to persistent differences countries and had the biggest collaboration network in the dyslexia research.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, medium-term significant effects on the outcome measures were found in a longitudinal study [26]. RRT efficacy was recently confirmed in a study testing the effect of a telerehabilitation version of the intervention [27].…”
Section: Introductionmentioning
confidence: 82%
“…In the same year, another Italian study ( Bonacina et al., 2015 ) tested the efficacy of a rhythm-based computerized program, called Rhythmic Reading Training (RRT), to improve reading in students with DD ( Cancer et al., 2016 , 2019 , 2021 , 2022 ; Cancer and Antonietti, 2017 ). The program included beat-based reading exercises, in which children would synchronize their reading to an isochronous beat.…”
Section: Music and Reading Training Combinedmentioning
confidence: 99%